Pregnant Women's Knowledge And Attitudes About High-Risk Pregnancy: The Effect of Using the JIPH Educational Application - Nawir, Farming; Kartini; Sitti Aisa; Fitriati Zabur (Public Health of Indonesia, 2025)
Background:Early detection and screening of risk factors among pregnant women are essential efforts to identify potential risks during pregnancy. The impacts of these risks may include miscarriage, obstructed labor, antepartum hemorrhage, stillbirth, pregnancy-related poisoning, premature birth, low birth weight, and maternal mortality. Given the high incidence of risky pregnancies, healthcare workers are unable to identify all cases individually. Therefore, the involvement of the community in detecting pregnancy risks is crucial. A tool is required to allow pregnant women or community members to independently assess pregnancy risks, with results that can be accessed by healthcare workers through the JIHP education application. Objective:This study aimed to evaluate the knowledge and attitudes of pregnant women after receiving education through the JIHP Android application. Method:A quasi-experimental design was used for this study, with a sample of 100 pregnant women divided into two groups: the intervention group (who received education through the JIHP Android application) and the control group (who did not receive education via the ebumil application). Simple random sampling was applied. The study variables were the knowledge and attitudes of pregnant women, and data were collected using questionnaires on these two aspects. The Wilcoxon test was used for data analysis. Results:The findings indicated a significant increase in knowledge among the intervention group, from a pre-test score of 81.10 (post 1) to 91.50 (post 2), while the control group showed no increase, with scores of 45.75 (post 1) and 45.50 (post 2). Similarly, attitudes improved in the intervention group, with scores rising from 79.40 (post 1) to 90.25 (post 2). In contrast, the control group showed no change in attitudes, with scores of 45.80 (post 1) and 45.75 (post 2). The Wilcoxon test yielded a p-value of 0.000, which is less than α = 0.05, indicating a significant effect of the education provided through the JIHP application on the knowledge and attitudes of pregnant women regarding risky pregnancies. Conclusion:The study concludes that education through the JIHP application significantly influences the knowledge and attitudes of pregnant women about high-risk pregnancies. Furthermore, there was a notable improvement in both knowledge and attitudes following the education intervention. It is expected that pregnant women will be able to apply the online knowledge gained to make informed decisions in managing their pregnancies.   Keywords:knowledge; attitude; Jaga Ibu Hamil Pesisir application